KAJIAN PENINGKATAN PRODUKTIVITAS PADI SAWAH MELALUI PENGELOLAAN HARA SPESIFIK LOKASI (PHSL) PADA LAHAN BERPOTENSI HASIL RENDAH - Abdullah, Syahrial (Jurnal Penelitian Pertanian Terapan, 2016)
The experiments was conducted at Kasang village, district of Batang Anai, Padang Pariaman regency during June until December 2013. The objectives of this experiment was to increased lowland rice production through specific location of nutrient management (SLNM) on low potential productivity of lowland. Four packages of fertilization such as Package A, B, C and D were arranged in Randomized Completely Block Design (RCBD) with 6 replications. Result of this experiment showed that; (1) SLNM treatments were significantly affected plant growth such as tiller number and plant high. Saveral of yield components also significantly affected by SLNM treatments packages such as panicles number, number of seeds per panicle, and percentage of filled grains. SLNM package A, B, and C significantly increased grain yields such as 24.9%,  34.2%, and 29.5% respectively compred to farmer package (Package D). The low grain yield with Famer package caused insufficient nutrient supplied for plant growth and yield is due to low fertilizer application and inaccurate nutrient management. The experiment suggested that the best application of inorganic fertilizer should be followed or combined with organic fertilizer such as animal manure or compost and  the application of thus material should be in mature condition. Key Words:  rice, specific location, fertilizer